2007
DOI: 10.1002/eji.200636719
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of endogenous apoptotic DNA and IFN‐α in complement C4‐deficient mice: Implications for induction of systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE), an autoimmune disease characterized by chronic nephritis, arthritis and dermatitis, and the presence of antinuclear autoantibodies, is associated with complement factor deficiencies in the classical activation pathway. In addition, IFN-a seems to be a key cytokine in SLE as an activated IFN-a system is regularly observed in patients with SLE. Here, we demonstrate that in lupus-susceptible, complement C4-deficient mice the lack of complement results in elevated intravascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…ITGAM (CD11b) expression was shown to increase DNA fragmentation, a prerequisite for apoptosis, and the level of fragmented DNA is increased in intravascular cells, which induces interferon α in SLE mice 9. CD11b also induces tumour necrosis factor α10 and modulates the innate immune mechanism11 in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…ITGAM (CD11b) expression was shown to increase DNA fragmentation, a prerequisite for apoptosis, and the level of fragmented DNA is increased in intravascular cells, which induces interferon α in SLE mice 9. CD11b also induces tumour necrosis factor α10 and modulates the innate immune mechanism11 in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the binding of complement to apoptotic and necrotic cells can lead to opsonization and phagocytosis by macrophages, which can also affect the amounts of DNA that can enter the circulation. These proteins may also bind directly to DNA and therefore modulate its extracellular trafficking [30–38]. Among these humoral factors, complement appears to play an important role in determining disease susceptibility as exemplified by the development of lupus in humans with hereditary deficiency of C1q and C4 as well as the corresponding murine models.…”
Section: The Role Of Cell Death In the Generation Of Extracellular Dnamentioning
confidence: 99%
“…This could be a result of presentation of their cognate antigen in a tolerogenic environment, as it has been found that DCs induce immunity or tolerance depending solely upon their activation status . However, in the present study this explanation appears unlikely, given the established general proinflammatory environment in 564Igi mice , C4‐deficient mice , and 564Igi C4‐deficient mice in particular . Consequently, we speculate that it is an active dominant‐negative tolerance mechanism, mediated probably by forkhead box protein 3 (FoxP3) + regulatory T cells (T regs ).…”
Section: Discussionmentioning
confidence: 56%